2021
DOI: 10.1038/s41598-021-86513-7
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning deficits in cervical dystonia point to defective basal ganglia circuitry

Abstract: Dystonia is conceptualized as a network disorder involving basal ganglia, thalamus, sensorimotor cortex and the cerebellum. The cerebellum has been implicated in dystonia pathophysiology, but studies testing cerebellar function in dystonia patients have provided equivocal results. This study aimed to further elucidate motor network deficits in cervical dystonia with special interest in the role of the cerebellum. To this end we investigated motor learning tasks, that differ in their dependence on cerebellar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…For instance, a visuomotor adaptation study in essential tremor patients found specific impairments in adaptation to a visual perturbation which were not associated with an inability to perform goal-directed movements, thus corroborating a cerebellar dysfunction hypothesis underlying ET ( Hanajaima et al, 2016 , Bindel et al, 2022 ). On the other hand, intact visuomotor adaptation found in patients with cervical dystonia may provide evidence for deficits along the cortico-basal-ganglia loop rather than cerebellar involvement in dystonia ( Loens et al, 2021 ). Nonetheless, due to the variable extent of cerebellar involvement in clinical populations, such studies can provide only limited evidence to involvement of the cerebellum in the process of visuomotor adaptation.…”
Section: Sensorimotor Adaptationmentioning
confidence: 99%
“…For instance, a visuomotor adaptation study in essential tremor patients found specific impairments in adaptation to a visual perturbation which were not associated with an inability to perform goal-directed movements, thus corroborating a cerebellar dysfunction hypothesis underlying ET ( Hanajaima et al, 2016 , Bindel et al, 2022 ). On the other hand, intact visuomotor adaptation found in patients with cervical dystonia may provide evidence for deficits along the cortico-basal-ganglia loop rather than cerebellar involvement in dystonia ( Loens et al, 2021 ). Nonetheless, due to the variable extent of cerebellar involvement in clinical populations, such studies can provide only limited evidence to involvement of the cerebellum in the process of visuomotor adaptation.…”
Section: Sensorimotor Adaptationmentioning
confidence: 99%